Leishmaniasis causes oxidative stress and alteration of oxidative metabolism and viability of neutrophils in dogs - Almeida, B. F M; Narciso, L. G.; Melo, L. M.; Preve, P. P.; Bosco, A. M.; Lima, Valéria Marçal Felix de [UNESP]; Ciarlini, Paulo Cesar [UNESP] (Elsevier, 2013)
The aim of the present study was to test the hypothesis that oxidative stress and alteration of oxidative metabolism and apoptosis of neutrophils in dogs vary with the stage of leishmaniasis and to determine the contribution of uremia to such alterations. Dogs with leishmaniasis were classified into two stages: moderate (Leish II, n = 20) or very severe (i.e. with concurrent uremia; Leish IV, n = 20) according to the LeishVet Consensus. The two leishmaniasis groups were compared with uremic dogs without leishmaniasis (Uremic, n = 10) and to healthy dogs (Control, n = 30). To determine oxidative stress, total antioxidant/oxidant capacity, lipid peroxidation, total glutathione and the plasma antioxidants albumin, uric acid and bilirubin were quantified. Superoxide production was determined using the hydroethidine probe and viability and apoptosis were measured using annexin V-PE by capillary flow cytometry. Oxidative stress was present in both uremia and leishmaniasis with reduced total antioxidant capacity and was associated with increased induced production of superoxide and apoptosis. The greatest amount of oxidants was observed in animals with moderate disease only. Neutrophils from uremic dogs with and without leishmaniasis had decreased viability and an increased apoptosis rate in addition to increased lipid peroxidation. In conclusion, oxidative stress occurs in both stages of leishmaniasis with differences in intensity and levels of plasma markers; however, uremia does contribute to the decreased spontaneous viability of neutrophils in dogs in the final stage of the disease. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Antioxidant status; Dog; Leishmania spp.; Oxidant status; Polymorphonuclear neutrophils